The Rhetoric of Qaṣr as a Linguistic Phenomenon in the Qur'an: A Study of the Verses of Tawheed - Muh Ilham; Haniah Haniah (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This investigation examines qaṣr, a rhetorical device denoting exclusivity, as both a linguistic and theological phenomenon within the Qur’anic verses of tawḥīd (divine oneness). Although classical balāghah scholarship has historically acknowledged qaṣr, its more profound epistemological and performative dimensions remain insufficiently explored, particularly in dialogue with contemporary linguistic theories. Employing a qualitative library search methodology, this research systematically analyzes authoritative classical texts alongside peer-reviewed international literature (2021–2024) to elucidate how qaṣr functions not merely as a stylistic ornament but as a mechanism that constructs meaning. The study identifies four distinct patterns: qaṣr ikhtirāṣ, syntactic inversion, implicit exception, and paired negation-affirmation, each strategically employed in key Qur’anic passages to affirm divine unity and refute polytheism. Findings indicate that qaṣr functions as an illocutionary act: it does not simply describe tawḥīd but enacts it, thereby shaping the believer’s theological consciousness. This research contributes theoretically by integrating classical balāghah with pragmatic and discourse-analytic frameworks, proposing a model termed “Qur’anic Rhetorical Pragmatics.” Practically, it provides a hermeneutical perspective for contextual and critical engagement with tawḥīd within pluralistic societies and pedagogical contexts. Ultimately, the study affirms that the linguistic architecture of the Qur’an is inherently theological, where form and faith converge to create an unambiguous understanding of divine Tawheed.